The First Livebirth Using Warmed Oocytes by a Semi-Automated Vitrification Procedure - Brunetti, Xavier Orriols (J Reprod Infertil, 2021)
BACKGROUND: The first successful livebirth using warmed oocytes (vitrified by the GAVI(TM) system) is reported in this paper. Embryologists throughout the world have vitrified oocytes using a manual technique which is susceptible to error and variation. In this era of automated laboratory procedures, vitrification was made semi-automatic by using the GAVI(TM) system. CASE PRESENTATION: Donor oocytes were initially vitrified using the GAVI(TM) system. They remained in the clinic’s oocyte bank until they were allocated to the patient. Donor oocytes were warmed as per Genea BIOMEDX protocol and inseminated to create embryos. Resulting embryos for the 42-year-old patient were cultured to the blastocyst stage, biopsied to perform PGT-A, using next generation sequencing and subsequently vitrified. The patient underwent a single euploid transfer in a frozen embryo transfer cycle which resulted in a healthy livebirth. CONCLUSION: The introduction of a semi-automated system should minimize the risk to the oocytes, standardize the procedure worldwide and potentially reduce the laboratory time taken by the embryologists. This case report demonstrates the safety of the technology used for vitrification, but larger randomized studies need to be performed to demonstrate the safety and efficacy of newer technologies like the GAVI(TM) system before adopting it as a standard laboratory procedure.